MODEL PENGENDALIAN ORGANISASI PADA PERUSAHAAN KELUARGA - Darsono, Darsono; Pamudji, Sugeng (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2003)
Family firms have been dominated national economy. However, some of them go bankrupt when handled by third generation. The owner-manager doesn't calculate a complexity of responsibility when the company become bigger and bigger. He thinks the same paradigm all the time. To overcome that problem, we propose a family-firm model with different control on it. As Ouchi (1980) said that three controls model can be used, ie. market, bureaucracy, and clan.